The Effectiveness of Al-Quran Memorization Methods for Millennials Santri During Covid-19 in Indonesia - Sardjana Orba Manullang; Mardani Mardani; Aslan Aslan (Nazhruna: Jurnal Pendidikan Islam, 2021)
This research discussed the effectiveness of memorizing the Koran online for the Muslim millennial generation in Indonesia. The success of memorizing Allah's word for the Muslim generation in the millennial era is greatly influenced by the learning and training system. One aspect of learning is selecting and applying methods that are believed to be useful in memorizing the Koran. To obtain material for discussing this theme, we have conducted a series of data searches through Google Scholar and the Education Research Information Center. After the data is collected, it is then analyzed critically, involving in-depth coding and interpretation systems. The data analysis process begins with an understanding of the problem's theme and is then linked with data that will answer questions before being taken as findings with validity and reliability principles. By paying attention to the literature and publication review data about the effectiveness of the memorization method, it can be concluded that our findings include that the method of memorizing the Koran is practically very useful in learning in the Quran memorization foundation with all the advantages of this online web application. Thus these results will add new knowledge for many parties.